In-Cylinder Heat Transfer Model Proposal Compatible with 1D Simulations in Uniflow Scavenged Engines - Héctor Climent; Andrés Tiseira; Josep Gomez-Soriano; Aditya Darbhamalla (Applied Sciences, 2023)
Advanced two-stroke engines are considered as powertrains for range extenders in hybrid electric vehicles due to size, simplicity, cost, and power density advantages. In-cylinder heat transfer is a phenomenon that affects the temperature of burnt gases and fresh air in an internal combustion engine. Compared to four-stroke units, this influence is more critical in two-stroke engines during the scavenging process since the gases velocity field inside the cylinder evolves rapidly in space and time. This study proposes a new convective heat transfer coefficient model beyond those based on Reynolds number calculation with the mean piston velocity. The model uses semi-empirical equations with non-dimensional numbers since it has to be integrated within the frame of a physical engine model, where thermo- and fluid dynamic properties of the gases inside the engine are solved using 0D or 1D approaches. In this particular application, the temperature deviation led to a poor prediction of trapped mass in the cylinder. The proposed convective heat transfer coefficient is calculated using a pseudo-velocity of the gases inside the cylinder based on the mass flow rates in the intake and exhaust ports during scavenging. The experimental results validate the 1D engine physical model, which is then used as initial conditions for CFD simulations. These CFD results are used to deduce the necessary conclusions for enhanced temperature predictability during scavenging, where deviations of less than 2% can be observed and an impact of up to 12% on the in-cylinder trapped mass can be seen.